Giant mucinous cystadenocarcinoma of ovary in a young woman: a case report and review of literature - Zhu, SiHong; Yao, MeiZhen; Xiong, LingNa; Tan, BuZhen (Frontiers in Oncology, 2024)
In April 2023, we successfully treated a 21-year-old patient afflicted with a rare giant cystadenocarcinoma, an extraordinarily large mucinous ovarian tumor that weighed nearly 25 kg. The preoperative dimensions of the tumor measured 40 × 30 × 34 cm, with the tumor’s weight nearing 25 kg. Despite its uncommon nature, we elected to perform a right adnexectomy, greater omentectomy, and peritoneal biopsy during the surgical intervention due to the patient’s youth and the family’s expressed desire to preserve fertility. In the subsequent August follow-up, CT scans revealed the complete resolution of the tumor, accompanied by the normalization of tumor markers, indicating a favorable outcome.